Study on Essential Derivation in Maize: III. Selection and Evaluation of a Panel of Single Nucleotide Polymorphism Loci for Use in European and North American Germplasm. Issue 3 (1st May 2015) - Rousselle, Yves; Jones, Elizabeth; Charcosset, Alain; Moreau, Philippe; Robbins, Kelly; Stich, Benjamin; Knaak, Carsten; Flament, Pascal; Karaman, Zivian; Martinant, Jean‐Pierre; Fourneau, Michael; Taillardat, Alain; et al.
ABSTRACT: Pairwise distance data for maize ( Zea mays L.) inbred lines generated using sets of single nucleotide polymorphisms (SNPs) selected from a 50k Infinium array were compared with pairwise distances generated using a set of 163 simple sequence repeat (SSR) loci previously identified to help determine essentially derived variety (EDV) status (UPOV, 1991). Final comparisons were made using 26, 874 SNPs after discarding SNPs with insufficient data quality or vulnerability to ascertainment bias. Inbred lines developed in the United States or in western Europe that had been previously published to establish SSR‐based thresholds provided the means to determine equivalent SNP‐based protocols. Use of 3072 SNPs selected to provide even genomic coverage according to genetic and physical maps provided robust, precise, high discrimination among inbred lines with consistent zonal classification with up to 20% missing data. Comparisons of intercepts and slopes for SSR and SNP inbred pairwise distance data translated the 82% SSR green‐orange similarity threshold to 91% using SNPs and the 90% SSR orange‐red threshold to 95% using SNPs. Information required to conduct analyses using these 3072 SNPS is presented.